Artificial Intelligence and Journalism in Pakistan: An Investigation of Journalists’ Attitudes and Adoption - Amna, Amna Khurshid (Journal of Peace, Development and Communication, 2023)
This article seeks to evaluate Pakistani journalists’ perspectives regarding the artificial intelligence journalism discipline (AIJ). As AI continues to penetrate various industries, including journalism, it is imperative that professionals working within those fields gain a better understanding of its advantages and disadvantages. This investigation explores the advantages and drawbacks of AI integration into journalism in Pakistan and its effect on journalists’ work. By investigating AI’s place in journalism and how best it may be deployed, this article hopes to open up dialogue regarding such technology’s potential implications and drawbacks. This study employed an online survey to gather information about Pakistani journalists’ knowledge and awareness of artificial intelligence journalism applications. Descriptive statistics were then used to analyze each question’s results; findings indicated that AI technology is already being utilized to some extent in Pakistani media outlets; a more widespread implementation may yet occur throughout society.